Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Assembly, annotation, and comparative whole genome sequence of fusarium verticillioides isolated from stored maize grains - Navale, Vishwambar D.; Sawant, Amol M.; Gowda, Varun U.; Vamkudoth, Koteswara Rao (2022)
Fusarium verticillioides is a plant pathogenic fungus affecting a wide range of crops worldwide due to its toxigenic properties. F. verticillioides BIONCL4 strain was isolated from stored maize grain samples in India, and produces high amount of fumonisin B1 (FB1). We report a comparative genomic analysis of F. verticillioides, covering the basic genome information, secretome, and proteins involved in host-pathogen interactions and mycotoxin biosynthesis. Whole-genome sequencing (WGS) was performed using the Illumina platform with an assembly size of 42.91 Mb, GC content of 48.24%, and 98.50% coverage with the reference genome (GCA000149555). It encodes 15,053 proteins, including 2058 secretory proteins, 676 classical secretory proteins, and 569 virulence and pathogenicity-related proteins. There were also 1447 genes linked to carbohydrate active enzymes (CaZymes) and 167 genes related to mycotoxin production. Furthermore, F. verticillioides genome comparison revealed information about the species' evolutionary history. The overall study helps in disease prevention and management of mycotoxins to ensure food safety.
Keywords: comparative genomics; Fusarium verticillioides; mycotoxin biosynthesis; plant-pathogen interaction; Secretome; whole-genome sequencing

Metabolomic profiling unravels the role of sphingolipid pathways in spot blotch resistance in wheat - Yadav, Sagar; Maiti, Saborni; Mundhe, Swapnil; Kadoo, Narendra (Acta Physiologiae Plantarum, 2025)
Spot blotch, caused by the soil- and air-borne fungal pathogen Bipolaris sorokiniana, is a major threat to wheat production. The disease is reaching epidemic proportions in wheat-growing areas, particularly in South Asia, South America, Africa, and Australia. In India, over 25 million hectares of wheat-growing area is threatened by this disease. A systematic study of metabolites can provide insights into the molecular basis of this disease. In the present study, we evaluated the impact of B. sorokiniana inoculation on two wheat varieties, Chirya3 (resistant to spot blotch) and DDK1025 (susceptible to spot blotch). We performed time-course non-targeted metabolite profiling of the pathogen-inoculated and mock-inoculated plants using liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS). Multivariate analysis was performed to construct a comprehensive statistical workflow, which led to the defined ``metabolomic phenotypes''. Modeling by Orthogonal Projection to Latent Structures-Discriminant Analysis (OPLS-DA) revealed significant metabolites in responses of the resistant and susceptible varieties to pathogen inoculation. A total of 699 metabolites displayed significant variations during the progression of infection. B. sorokiniana-inoculated Chirya3 exhibited high levels of some metabolites, such as sphingolipids, cysteine, phenylalanine, shikimates, etc. The study revealed that sphingolipid pathways are critical in resistance mechanisms contributing to enhanced lignification and disease resistance in wheat.
Keywords: Cochliobolus sativus; High-resolution mass spectrometry; LC-HRMS; Metabolite profiling; OPLS-DA; plant-pathogen interaction

Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics